Study of adsorption efficiency of different metal ions over CaCO3 extracted from tap water - Bansal, Mehak (My University, 2019)
This present work describes the extraction and characterization of CaCO3 extracted from boiling tap water and examines its adsorption efficiency for the removal of different metal ions(Mn+7, Cr+6, Cu+2, Ni+2). The extracted CaCO3 was calcined at 400˚C and 900˚C. The CaCO3 is characterized by using DLS, ZETA, SEM, TGA and UV-Visible spectroscopy techniques. The CaCO3 was also used to investigate its adsorption property for the removal of different metal ions. DLS measurements showed that the particle size distribution of CaCO3 lies in the range from 0.63 μm to 1.27μm. The surface morphology shows the chips, flakes, rods, sphere- like shapes and the particle size lies in between 1μm to 2μm. Zeta potential and surface charge of CaCO3 -900˚C is negative in nature because the CaCO3 decomposed into CaO and form Ca(OH2). The impact of adsorption of different metal ions (Mn+7, Cr+6, Cu+2, Ni+2) over CaCO3 with different time intervals was also studied. The Langmuir adsorption isotherm is the best fit adsorption isotherm for this work. The kinetics studies follow the first order reaction. Mn+7 adsorb at higher efficiency among all the metal ions. It was concluded CaCO3 material will be very effective for adsorption and removal of different metal ions.
Keywords: Room Temprature; Dynamic Light scatter; Calcium Carbonate; thermometric analog